An approximation delay between consecutive requests for congestion control in unicast CoAP-based group communication - Chanwit Suwannapong; Chatchai Khunboa (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This research presents a way to avoid network congestion during unicast CoAP-based group communication using increased delays between consecutive requests (DCR) in LoWPAN border routers to limit request send rates. It also provides a way to determine DCR values that are suitable for various network group sizes with differing node counts. The optimal DCR is obtained using the least squares approximation method and the relative minimum. Results from experimentation shows a positive relation, that is, an increase in group size necessitates an increase in DCR value. Experiments in various group sizes show favorable network performance and support the proposed congestion control method using DCR.